Architectural Design of the Temple of Olympian Zeus in Akragas (c. 480 B.C.) - Boyko, Elizaveta A. (Actual Problems of Theory and History of Art, 2023)
The article examines the design of the temple of Olympian Zeus in Akragas built under the tyrant Theron the Emmenide (488–472 B. C.). The author highlights the following features of its architecture: the size of the building and the rich sculptural decoration, merging of the outer colonnade with the wall, the shape of the supports in the outer colonnade, which is a combination of semi-columns on the outer side and pilasters on the inner, an odd number of supports on the front side, and the absence of an entrance in the center of the facade. At first view, the temple of Zeus is worth comparing with the Ionian dipteral temples of the 6th century B. C., which probably represented a specific way of glorifying the tyrants under whose rule they were built. However, upon closer examination, it has turned out that in addition to the idea of prosperity under the rule of a tyrant, the temple of Zeus reflected the trends common in Greek lands in general, and in Italy in particular. Among the analogies in terms of size and dedication, we can single out the temple of Olympian Zeus in Athens, and in terms of architectural design, a number of temples in Magna Graecia and Sicily.